2005
DOI: 10.1097/01.pas.0000170348.40057.60
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Mucin-Producing Sweat Gland Carcinoma

Abstract: Endocrine mucin-producing sweat gland carcinoma (EMPSGC) is an underrecognized low-grade carcinoma with predilection to the eyelid. Only 4 cases of this entity have been described in the literature. Here, we describe 12 cases of EMPSGC. The lesions were twice as frequent in females than males with an average age of 70 years (range, 48-84 years). Clinically, they presented as a slowly growing cyst or swelling. The most common site of occurrence was the lower eyelid (8 cases). Two lesions occurred on the upper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 17 publications
2
79
0
1
Order By: Relevance
“…EMPSGC is a rare adnexal tumor that is twice as common in females [13, 6] and with a predilection for the face, particularly the eyelids [16]. It tends to occur in individuals in their 6th and 7th decades of life [13, 6].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…EMPSGC is a rare adnexal tumor that is twice as common in females [13, 6] and with a predilection for the face, particularly the eyelids [16]. It tends to occur in individuals in their 6th and 7th decades of life [13, 6].…”
Section: Discussionmentioning
confidence: 99%
“…It tends to occur in individuals in their 6th and 7th decades of life [13, 6]. The entity was first coined by Flieder et al in 1997 [7] and since then, less than 60 cases have been reported in the literature, making it an uncommon skin tumor that may pose diagnostic challenges to clinicians and pathologists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations